Practice-oriented tasks as a way to develop future engineers’ skills of mathematical modelling - Mechik S. V., Osintseva M. A. (Humanitarian, 2017)
the article describes the possibilities of developing modelling skills in the process of teaching students at engineering faculties mathematics by means of practice-oriented problems solving.
Keywords: математика; математическое моделирование; mathematics; практико-ориентированные задачи; mathematical modelling; practice-oriented problems